Estrategias metodológicas y su incidencia en el aprendizaje en el área de CCNN en los estudiantes de 3ero educación general básica de la Unidad Educativa “Juan E Verdesoto” - Reyes Sánchez, Meybeth Anahi (2023)
This project will focus its study on the application of methodological strategies as it will have a significant impact on learning in the area of CCNN in 3rd grade E.G.B. students of the "Juan E. Verdesoto" School. In the Juan E. Verdesoto Educational Unit, in the Babahoyo canton, third grade students face difficulties when analyzing the natural events that surround them, sometimes they misinterpret them or assign them to non-natural causes, creating confusion in the learning process and the acquisition of knowledge in a habitual way. As results of the surveys to the teachers, it was evidenced that a considerable percentage of the teachers make use of the school text to plan and guide the subject, likewise, from their observations, it was identified that the teachers used the school text to carry out activities such as the development of tasks and, in a lower percentage, those of dissemination and evaluation. That is why we seek to encourage teachers to improve their methodological strategies in the process of teaching the area of natural sciences and to have the necessary resources when teaching this subject, so that students can develop all their skills and build knowledge while learning, with all the will to learn and improve their academic performance.